MICROSPHERE-BASED FLOW CYTOMETRY PROTEASE ASSAYS FOR USE IN PROTEASE ACTIVITY DETECTION AND HIGH-THROUGHPUT SCREENING - Saunders, Matthew J. (Curr Protoc Cytom, 2010)
This protocol describes microsphere-based protease assays for use in flow cytometry and high-throughput screening. This platform measures a loss of fluorescence from the surface of a microsphere due to the cleavage of an attached fluorescent protease substrate by a suitable protease enzyme. The assay format can be adapted to any site or protein specific protease of interest and results can be measured in both real time and as end point fluorescence assays on a flow cytometer. End point assays are easily adapted to microplate format for flow cytometry high-throughput analysis and inhibitor screening.